The Use of Solar Collectors in Domestic Hot Water Systems in Central and Eastern European Countries: Simulation in TRNSYS - Ołtarzewska Agata; Krawczyk Dorota Anna (Environmental and Climate Technologies, 2023)
Solar collectors are devices that enable the use of solar radiation, e.g., for hot water preparation or space heating. They are playing an increasingly important role in Europe and around the world, mainly due to the easy availability of the sun, as an energy source. The advisability of their use depends on a number of factors, of which climatic conditions are an extremely important one. This paper presents the results of energy simulations of a solar collector-based domestic hot water system for the capitals of five selected Central and Eastern European Countries (CEEC): Riga, Warsaw, Prague, Bratislava, and Zagreb. Using TRNSYS software, a theoretical model of the system was developed and dynamic simulations were carried out for the entire year. The amount of useful energy generated by the flat-plate collectors, their efficiency, as well as the auxiliary energy requirements and the amount of energy needed to meet the load were estimated and compared. The extent to which changing the area of solar collector affects the operation and efficiency of the system for different locations was also analysed. The results showed that in terms of efficiency, the use of solar collectors is most favourable in placed southernmost Croatia and in Slovakia, where it was also achieved the lowest annual auxiliary energy demand. The least favourable location turned out to be Riga. It is also worth noting that regardless of location, the area of solar collector has a significant impact on the efficiency of the entire system.